2019
DOI: 10.1111/his.13943
|View full text |Cite
|
Sign up to set email alerts
|

SATB2 in neuroendocrine neoplasms: strong expression is restricted to well‐differentiated tumours of lower gastrointestinal tract origin and is most frequent in Merkel cell carcinoma among poorly differentiated carcinomas

Abstract: Aims Special AT‐rich sequence‐binding protein 2 (SATB2) is a transcriptional regulator with critical roles in brain, craniofacial and skeletal development. It has emerged as a key marker of lower gastrointestinal (GI) tract columnar epithelial and osteoblastic differentiation. Transcription factor immunohistochemistry is useful in assigning site of origin in well‐differentiated neuroendocrine tumours (NETs), and has had a limited role in poorly differentiated neuroendocrine carcinomas (NECs). This study sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 41 publications
(80 reference statements)
1
28
0
Order By: Relevance
“…15 SATB2 is highly sensitive and specific for lower gastrointestinal tract origin of a neuroendocrine tumour, particularly for well-differentiated neoplasms. 16 Neuroendocrine carcinoma of the lower gastrointestinal tract demonstrates similar high expression, however metastasis from a non-gastrointestinal Multiple possibilities: CK7, CK20, TTF1, CDX2, SATB2, GATA3, PAX8, ER, calretinin, CK5/6, S100, SOX10, CD3, CD20 EBV, Epsten-Barr virus; MMR, mismatch repair; IBD, inflammatory bowel disease; IPMN, intraductal papillary mucinous neoplasm.…”
Section: Satb2mentioning
confidence: 99%
See 1 more Smart Citation
“…15 SATB2 is highly sensitive and specific for lower gastrointestinal tract origin of a neuroendocrine tumour, particularly for well-differentiated neoplasms. 16 Neuroendocrine carcinoma of the lower gastrointestinal tract demonstrates similar high expression, however metastasis from a non-gastrointestinal Multiple possibilities: CK7, CK20, TTF1, CDX2, SATB2, GATA3, PAX8, ER, calretinin, CK5/6, S100, SOX10, CD3, CD20 EBV, Epsten-Barr virus; MMR, mismatch repair; IBD, inflammatory bowel disease; IPMN, intraductal papillary mucinous neoplasm.…”
Section: Satb2mentioning
confidence: 99%
“…MINI-SYMPOSIUM: GASTROINTESTINAL/HEPATO-PANCREATO-BILIARY PATHOLOGY site needs to be excluded. 16 SATB2 also allows for separation of primary small intestinal adenocarcinoma from colorectal carcinoma that has spread to the small intestine. While most primary colorectal carcinomas express this protein, less than half of primary small intestinal adenocarcinomas do.…”
Section: Tablementioning
confidence: 99%
“…51 Higher expression of SATB2 gene has been reported in Merkle cell carcinoma, pancreatic, breast, colon, rectal and liver cancer patients than normal counterparts. 7-9,20,26, [52][53][54][55] The combination of SATB2 and CK20 was found to identify more than 95% of colorectal cancer. 52 Another study using 50 paired colorectal and normal tissues has reported an increased expression of SATB2 in colorectal cancer tissues.…”
Section: E Xpre Ss I On Of Satb2 In C An Cermentioning
confidence: 99%
“…SATB2‐associated syndrome (SAS) is an autosomal‐dominant neurodevelopmental disorder caused by changes in the gene expression of SATB2 51 . Higher expression of SATB2 gene has been reported in Merkle cell carcinoma, pancreatic, breast, colon, rectal and liver cancer patients than normal counterparts 7‐9,20,26,52‐55 . The combination of SATB2 and CK20 was found to identify more than 95% of colorectal cancer 52 .…”
Section: Expression Of Satb2 In Cancermentioning
confidence: 99%
“…It is also positive in 83–85% of CRCs and in 75% of appendiceal adenocarcinomas, while it is uncommonly expressed in adenocarcinomas of gastric and pancreatic origin [ 20 , 21 ]. Therefore, it has been recently proposed as a new highly tissue-specific and sensitive marker of lower intestinal tract origin in both adenocarcinomas and well-differentiated neuroendocrine tumors [ 21 , 22 ]. However, a fraction (up to 46%) of SBAs have been reported to exhibit SATB2 positivity [ 16 , 21 , 23 ], although studies on SATB2 expression in SBA are limited to relatively small series, which include very few SBAs associated with Crohn’s or celiac diseases.…”
Section: Introductionmentioning
confidence: 99%